Prekariat — nowa klasa społeczna? - Stencel, Michał (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Precariat is aglobal problem that needs to be overcome, but the effective ways to stop it are still being search for. Prof. Guy Standing in his book gave proposals for changes that could stop precariat. The main postulate of auniversal guaranteed income, which is alow salary from the state supplemented by income from ad hoc work. Besides postulates of asystemic change in income redistribution for example: taxes or tax credit, amental and systemic change is suggested in the system of banking and insurance as well as alegally specified maximum income, common goods, limiting corporate power and strengthening of civil society. The methods of countering the problem are various depending on the views. It will surely be along fight and it requires anumber of socioeconomic changes. The European Union began his fight with precariat — 24 countries meeting in Paris, in November 2013, have decided on aguarantee of employment for young people within two years. The program is called “guarantee for the young” and it stipulates that any person under 25 years of age without ajob is offered apost, training or practice within four months. This project also implies: encouraging young people to raise the education and undertake new training, providing assistance in entering the labor market or teaching entrepreneurship and motivating young people to start their own businesses. But the question arises here whether some of these proposals are not a problem of precarity right now? Governments should realize that this problem can no longer be concealed. The patience of the group is already exhausted and now it is starting to go out on the streets and cause big problems.
Keywords: prekariat; prekaryjność; bezrobocie wśród młodych; klasa społeczna; pracujący biedni; konflikt społeczny